PENGEMBANGAN USAHA PENANGKAPAN GURITA DI KECAMATAN PULAU SEMBILAN, KABUPATEN SINJAI - Pradilia, Andi Desiah; Gani, Imam Prawiranegara; Saiful, Saiful; Sudirman, Azisah Azzahra (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
This study aims to identify and formulate effective strategies in octopus fisheries in Pulau Sembilan District. The approach used in this study is qualitative, with descriptive analysis and case studies on octopus fisheries business actors in the area. Data were obtained through in-depth interviews with fishermen, entrepreneurs, others, as well as field observations, literature reviews, and related parties. The results of the study indicate that octopus fisheries in Pulau Sembilan District have great potential but face several challenges, including market price fluctuations, technological limitations, and problems in resource management and marketing. SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis revealed that the main strengths are self-made and easily obtained fishing gear and profitable fishing efforts, while weaknesses include the low bargaining position of fishermen. Development opportunities include the availability of octopus market demand, while threats include fluctuating catch volumes and the entry of fishing fleets from other areas that use environmentally unfriendly tools. The recommended development strategy includes optimizing fishing groups and developing fishing gear that supports fishing activities to ensure business sustainability. The implementation of this strategy is expected to increase the productivity, income and welfare of the fishing community in Pulau Sembilan District